'We shall recover, we shall overcome': An occupational therapist's reflection on the effect of occupational injustice on mental health during the pandemic of Covid–19 in South Africa. Issue 2 (3rd July 2021) - Scott, Ashley
ABSTRACT: This reflection article explores the effects of occupational deprivation on mental health in low and middle-income contexts, specifically in the South African Context. The effect of recommended Covid-19 strategies has a momentous effect on the mental health of those living in less-resourced areas, with those suffering having less influence over their ability to cope in tough times. Occupational therapists have an important role to play in advocacy for those struggling with their mental health through small actions to promote mental health both locally and globally.